On the Bruun Rule suitability for modelling shoreline change - Seenath, A; Jonathan, D (Elsevier, 2024)
Modelling and understanding shoreline response to sea-level rise over decadal to centennial timescales is crucial for managing sandy coasts. Globally, the Bruun Rule is one of the most common shoreline model applied to facilitate this. However, there are several limitations to the Bruun Rule, which can compromise coastal management decisions. Here, we provide a novel assessment of the suitability of the Bruun Rule for application in sandy coasts by applying it to hindcast and project shoreline change in three morphologically different sandy beaches over yearly and decadal timescales. We also compare the Bruun Rule predictions against associated observations, published predictions from a hybrid shoreline model, and historical shoreline changes. Results show that the Bruun Rule fails to accurately hindcast and provide realistic projections of future shoreline change in sandy coasts. We attribute this to its assumption of linearity between shoreline retreat and relative sea-level rise and its inability to account for nearshore circulation. We, therefore, recommend limiting the use of the Bruun Rule for informing policy and the management of sandy coasts.